Abandonment of prescriptions in medically underserved areas: Primary medication non-adherence in community pharmacies in the delta region of the United States - Minghui Li; Matthew Harmon; Mike Wasson; Lindsey Cardosi; Lindsey Henson; Hunter Hill; Brad Ian Jobe; Sydnee E. Hewitt; Kenneth C. Hohmeier (Elsevier, 2024)
Background: In the U.S. alone, medication non-adherence is estimated to cause 1 in 10 hospitalizations, approximately 125,000 deaths annually, and cost the U.S. healthcare system just under $300 billion each year. Patients in medically underserved areas (MUAs) are particularly vulnerable to all forms of non-adherence and downstream morbidity and mortality; however, the extent to which primary medication non-adherence (i.e., prescription abandonment) affects the underserved is still largely unknown. Objectives: To assess the difference in rates of abandonment of quality measured prescriptions in areas that are medically underserved compared to areas that are not. The secondary objective is to assess the impact that the COVID-19 pandemic had on rates of prescription abandonment in both MUAs and those that are not. Methods: In this retrospective study, data on abandoned, quality measured prescriptions were collected and analyzed using Chi-Square analyses from one regional division of a large grocery-chain pharmacy containing ninety-one pharmacies located in Tennessee, Mississippi, Arkansas, Kentucky, and Missouri. The primary objective used 2019 data while the secondary objective used data from April - November of both 2019 and 2020. Results: Patients from MUAs abandoned quality measured prescriptions at a higher rate of 5.44% compared to 4.77% of those not living in these areas (P < 0.01). This study also discovered that during the COVID-19 pandemic, MUAs had a decrease in abandonment from 6.14% in 2019 to 6.02% in 2020 (P < 0.01). Those from non-MUAs had non-significant change in abandonment (P = 0.87). Conclusion: Patients in MUAs abandon quality measured prescriptions at a statistically significant higher rate when compared to patients who live in areas that are not considered to be medically underserved. Moreover, during the COVID-19 pandemic patients living in MUAs had a statistically significant decrease in prescription abandonment while those in non-MUAs did not statistically change.